Sealab 2021. - Reed, Adam (Adam Brooks); Thompson, Matt (Warner Home Video, 2005)
Oh, what a difference a year makes. The crew of classic 1972 series Sealab 2020 has been replaced with a gang of misfits unfit for public service. Their mission: to investigate underwater colonization. They are doing a very bad job.